Upaya Pengurangan Risiko Bencana Tanah Longsor Melalui Implementasi Program Pengembangan Desa Tangguh Bencana Di Kota Sawahlunto - Friska Friska; Kusdarini Kusdarini; Roni Ekha Putera (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2021)
This study aims to describe and analyze efforts to reduce the risk of landslides by implementing a disaster-resilient village development program in the city of Sawahlunto. This research is motivated by the frequent occurrence of disasters such as floods, landslides, land fires, residential fires, mine blasts, and tornadoes. Under these conditions, efforts to reduce disaster risk, which is an effort to minimize disasters' impact, need to be done. One of the most critical efforts to reduce disaster risk is to increase community preparedness in facing disaster threats. This was implemented through the Resilient Disaster Village program. The findings and analysis of the data that the researchers presented according to the Donald Van Meter and Carl Van Horn policy implementation models The implementation of the Resilient Village Disaster Program Development in Sawahlunto City has been going well. However, it is still not evenly distributed in all implemented villages, and still, two villages are determined. In the Resilient Disaster Village Program Development implementation, two villages that have implemented the Resilient Disaster Village Program Development according to the Resilient Disaster Village Program Development's objectives have begun to be reached. The Lumindai village is in the Primary Resilient Disaster Village category, and until now, there has been no improvement, and the same was true of Silungkang Oso Village. This is due to several indicators, namely the Facilitator with a small number and understanding of the Resilient Disaster Village Program Development implementor is not yet in-depth towards the Development of the Resilient Disaster Village Program, resources, especially budget resources, are still inadequate implementor of the Resilient Disaster Village Development, and support from the community at each village government is different. The Development of the Resilient Village Program has been carried out but not yet optimally due to the lack of development in the village determined.